2004
DOI: 10.1023/b:joec.0000037747.74665.0a
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity and Defensive Properties of Norditerpenoid Alkaloids

Abstract: We have tested the insect antifeedant and toxic activity of 43 norditerpenoid alkaloids on Spodoptera littoralis and Leptinotarsa decemlineata including eserine (physostigmine), anabasine, and atropine. Antifeedant effects of the test compounds were structure- and species-dependent. The most active antifeedants to L. decemlineata were 1,14-diacetylcardiopetaline (9) and 18-hydroxy- 14-O-methylgadesine (33), followed by 8-O-methylconsolarine (12), 14-O-acetyldelectinine (27), karakoline (7), cardiopetaline (8),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 18 publications
4
31
2
Order By: Relevance
“…The only cost of anabasine consumption we detected was a 2-day delay in onset of egg laying, with no effect on the eventual number or mass of eggs and larvae. These results are in contrast to studies showing lethal and sublethal effects of anabasine on other insects [47]. Moreover, although bumblebees are known to be deterred from feeding by some secondary metabolites in nectar and pollen [48,49], bees in this experiment increased rather than decreased consumption of nectar containing a high concentration (20 ppm) of anabasine.…”
Section: Discussioncontrasting
confidence: 99%
“…The only cost of anabasine consumption we detected was a 2-day delay in onset of egg laying, with no effect on the eventual number or mass of eggs and larvae. These results are in contrast to studies showing lethal and sublethal effects of anabasine on other insects [47]. Moreover, although bumblebees are known to be deterred from feeding by some secondary metabolites in nectar and pollen [48,49], bees in this experiment increased rather than decreased consumption of nectar containing a high concentration (20 ppm) of anabasine.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous results have shown that T. cruzi mortality increased with ADs 13-oxo-cardiopetamine (inactive against L. infantum, data not shown) and 1, while 2 and 3 were inactive which suggests species-related selectivity for the anti-parasitic action of these compounds, with L. infantum being more sensitive to DAs than T. cruzi. Furthermore, none of 43 NDAs tested on T. cruzi affected its viability as shown here for L. infantum [10,15] indicating a strong molecular selectivity for the trypanocidal and leishmanicidal effect of DAs.…”
Section: Resultsmentioning
confidence: 72%
“…NDAs act as potent nicotinic cholinergic receptor (nAcChR) agonists and antagonists in invertebrates, including insects and in vertebrates [7]. The insecticidal and anti-feedant activity of NDAs [8][9][10], suggest a defensive role played by these compounds. However, only a few DAs have been studied for their plant defensive and pharmacological properties, including their effects on Trypanosoma cruzi epimastigote forms [9,[11][12][13][14][15] and their neurotoxic effects are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, in vitro antiviral, antibacterial, and antifungal activities of five diterpene-type of alkaloids (1)(2)(3)(4)(5) were determined ( Figure 1). The results pointed out that these alkaloids possessed the highest antibacterial activity against K. pneumoniae and A. baumannii (Table 1) at 8 µg/ml concentration, whereas they were moderately active to the rest of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…1 These plants have also been the cause of poisonings that primarily occur in cattle as well as human beings, due to toxicity of their alkaloids. [2][3][4][5] The common name of Consolida sp., shared with the closely related genus Delphinium, is "larkspur".…”
Section: Introductionmentioning
confidence: 99%